The impact of representative bureaucracies: educational systems and public policies - Meier Kenneth; Steward Joseph, Jr.
Studies of representative bureaucracies are staples of public administration research; however, because of a variety of methodological problems, too few have been able to address the basic "so what?" question. Do bureaucracies with different levels of representativeness produce different policy outputs and have different policy impacts? Our research addresses these inquiries using data from the 67 public school districts in Florida. The analysis shows that when we focus on (a) bureaucrats who exercise discretion, (b) a demographic factor with a lasting impact-race, and (c) policy measures that are clearly salient to the chosen demographic factor, we can detect the relationships between bureaucratic representati
Keywords: Bureaucracy -- U.S.A.